Implementation of Intercultural Communication Competence in Global Airline Services: A Case Study of Emirates Airline - Tiara Ayu Permatasari; Eunike Iona Saptanti (Prodi Ilmu Komunikasi UTM, 2026)
Efforts to accommodate global customer mobility often give rise to miscommunication in aviation services due to cultural disparities. Airline personnel are expected to possess effective communication competencies to navigate differences in language, values, and cultural norms to enhance customer satisfaction. This study aims to analyze the intercultural communication strategies implemented by Emirates Airline customer service in identifying the needs of customers from diverse cultural backgrounds and to evaluate the application of Intercultural Communication Competence (ICC). To comprehend lived experiences of the subjects, this research employs a descriptive qualitative approach. Data were collected through in-depth interviews with three customer service staff, selected through purposive sampling. The findings indicate that ICC is a mechanism in navigate Customer Services in facing cultural differences. Synchronization between Motivation, Knowledge and Skills has to be daily customer services practices. Motivation act as a internal drive and as an effort to respecting diversity. Intercultural knowledge provides foundation that enabled staff interpret values, norm, and language proficieny. Skills adapt verbal and nonverbal cues, as well as avoids misunderstanding. Aligned with Samovar, intercultural communication can be succeed if there are willingness to learn and integrating system to enhance service quality, satisfaction, and loyalty within the competitive international aviation industry.Keywords: Intercultural Communication; Customer Service; Communication Competence; Service Strategy; Emirates Airlines.